Appreciating Everyone’s Unique Contribution To The Jigsaw Puzzle of Education: Autonomy and Responsibility Journal Of Educational Sciences Vol. 9 No. 1 (2024) - Jacobs, George M. (Autonomy and Responsibility Journal of Educational Sciences, 2025)
This article focuses on increasing students’ appreciation of their groupmates’ contributions to successful group learning experiences, with special attention to nursing education. The article begins with looking at the Jigsaw technique and four aspects that power Jigsaw: everyone has a unique resource; everyone needs to cooperate to succeed; everyone strives together to achieve a group learning goal; and teachers facilitate student-student interactions. Next, the article looks at six other cooperative learning techniques and families of techniques. Finally, nine suggestions are made for helping all group members shine in Jigsaw, the other cooperative learning techniques, and, indeed, all group learning endeavours. The gap this article addresses is that while group activities may be common, insufficient attention is paid to the inner workings of peer learning.